Neural connectivity in youth at-risk for bipolar disorder: a review of functional magnetic resonance imaging studies - Santos, Vítor (2017)
Background: Delayed diagnosis of bipolar disorder (BD) is common in adolescents and young adults and the search for biomarkers to help in early diagnosis in BD at-risk populations is an important goal of neuroimaging research. Functional connectivity studies in BD patients suggests that anomalous connectivity between prefrontal and limbic regions could be risk biomarkers for BD. The aim of this review is to provide an overview of the neuroimaging literature that employed functional connectivity techniques in adolescents and young adults at-risk for BD. Methods: A literature search was conducted using PubMed and EMBASE databases, to identify fMRI studies that em- ployed a measure of functional or e ective connectivity or network based statistics and included individuals at-risk for BD who were in the age range of early-mid adolescence (13–18 years old) and/or young adulthood (19–25 years old). Results: Ten studies focusing on 4 functional imaging domains were identi ed, namely emotion processing, a ective cognition, reward processing and resting-state. Altered functional connectivity between amygdala and ventrolateral prefrontal cortex (PFC); amygdala and anterior cingulate cortex and between anterior cingulate cortex, ventrolateral PFC and dorsolateral PFC emerged as putative risk biomarkers. Heterogeneity in BD at-risk samples, tasks and connectivity analysis methods has been identi ed. Conclusions: Youth at-risk for BD have altered functional connectivity in prefrontal-limbic networks supporting emo- tion regulation that might underlie emotion lability and mood dysregulation predisposing to BD. Future longitudinal studies in adolescents and young adults with Bipolar At-Risk criteria are important to establish functional connectivity measures as risk biomarkers.